Seasonal Variations in Physicochemical Parameters of selected Wetlands in and around Coimbatore District. - Mercy. M; Sr. Mary Fabiola (International Journal of Pharma and Bio Sciences, 2020)
Fresh water is the prime resource of a country that has a unique place in all routine human activities. But as these fresh water bodies are getting contaminated, the present investigation was undertaken to analyze the physicochemical parameters of three prime wetlands of Coimbatore district for a period of one year (i.e. March 2018 to February 2019). As a result of our experimental analysis, the report showed remarkable seasonal changes in the water quality. But all the analyzed parameters were within the permissible limits (WHO) except certain parameters like turbidity, pH, dissolved oxygen which were recorded above the desirable limits. All the parameters were noted to be high in summer and low in winter and monsoon except Turbidity, pH and dissolved oxygen which was noted high during winter and low in summer. Thus, among the three selected wetlands Orathupalayam and Sulur wetland showed less water quality. So, the present finding states that Perur wetland is ecologically better in water quality than the other two wetlands.